A revision of the freshwater crab genus Hainanpotamon dai, 1995 (crustacea: Decapoda: Brachyura: Potamidae: Potamiscinae), with a Redescription of Potamon (Potamon) orientale (Parisi, 1916) and descriptions of three new species - Yeo, D.C.J. (2014)
10.2108/zsj.24.1143